Numerical classification and ordination of ruderal plant communities (Sisymbrietalia, Onopordetalia) in the western part of Slovakia - Mucina, Ladislav (1982)
The ruderal communities of the orders Sisyrnbrietalia and Onopordetalia from the western part of Slovakia have been subjected to numerical classification and ordination. The ordination techniques proved to be a useful tool in the elucidation of the cluster pattern as well as in the detection of the main environmental variation underlying the floristic variation within the data. Results obtained with numerical techniques and traditional syntaxonomical classification have been compared. The similarity between these results is low at the level of the orders. This incompatability is explained by the differences in the weighting of the species in the course of the classification process and by the addition of non-floristical criteria that often occurs insyntaxonomical classification according to Braun-Blanquet. The highest value has been observed at the 3-clusters level (both orders and the Malvion neglectae). High similarity among the results of the numerical techniques have been observed, particularly in the group of space-dilating clusterings (Ward's method, Complete linkage clustering and McQuitty's similarity analysis). Average linkage clustering produces the most diverse result. The Malvion neglectae appeared as a separate group in all numerical techniques adopted. This suggests the upranking of its syntaxonomical position. The Bromo-Hordeion murini turned out to be a very heterotoneous syntaxon.